Resolva as expressões abaixo:
a) [(-7) + (+4)] + (+3)=
b) (+5) - (+9)=
c) (+24) - (-12)
d) (-7) + [(+4) + (+3)]
Respostas
respondido por:
2
Resposta:
a) 0
b) -4
c) +36
d) 0
Explicação passo-a-passo:
Cálculos na imagem, ok?!
Anexos:
pamelapetrina1503:
muito obrigada
respondido por:
1
Resposta:
A:-7 + 4 = -3;
-3 + 3 = 0.
B:5 - 9 = -4;
C:24 - 12 = +12;
D:-7 + 4 = -3;
-3 + 3 = 0.
Explicação passo-a-passo:Espero ter ajudado!!
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás